Behavior of Small-Scale Concrete Cylinders in Compression Laterally Confined by Basalt Fiber and PEN Fiber Reinforced Polymer Composites - Batzaya Baasankhuu (International Journal of Concrete Structures and Materials, 2020)
Abstract Axial compression test was conducted to investigate the effect of confinement on plain concrete cylinders by wrapping polyethylene naphthalate fiber reinforced polymer (PEN FRP) with large rupture strain (LRS) capacity. To draw comparison on the confinement effect by PEN FRP wrapping, the confining effect by basalt FRP (BFRP) wrapping was also investigated. A total of 25 tests was completed. Test variables were two different FRP composites (PEN FRP, BFRP) and number of FRP layers (1, 2, 3 layers of PEN FRP and 2, 4, 6 layers of BFRP) in the main confinement tests (21 tests). In the additional confinement tests, the test variable was overlap length of PEN FRP (four tests). Confinement by BFRP and LRS PEN FRP was both effective as demonstrated by continuously ascending stress–strain relationship of the confined concrete. The PEN FRP wrapped concrete deformed more both axially and laterally to develop strength equivalent to that of the BFRP wrapped concrete. A simplified procedure for rational modelling of stress–strain relationship of the confined concrete was suggested. The suggested procedure is applicable for both BFRP and PEN FRP confined circular concretes on condition that basic confinement test data specific to the FRP composite are provided.